SIT dalam peta sistem pendidikan nasional - Suyatno, Broery (Universitas Ahmad Dahlan, 2015)
Integrated Islam schools emerged as a response to dissatisfaction Islamic movement activists against the national education system in Indonesia. National education system considered in the management of education perpetuates the dualism between religion and public education. Therefore, it takes a model of alternative educational institution capable of removing any educational practice dichotomous. During its development, paradox regarding the development of integrated Islamic school when they actually have to be part of the national education system. This study aims to answer the question of how the position of integrated Islamic schools in the National Education map? This study is a qualitative case study model. Data collection methods were participant observation, in-depth interviews, and documentation. Data was analyzed using inductive-qualitative analysis. The results showed that the integrated Islamic school is an integral part of the national education system. The indication is the adoption of the curriculum of the ministry of education and culture, adjustment of the examination system, and certification programs by teachers of integrated Islamic school.